Situation Report: Bulgaria, 5 March 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Central Committee Plenum on Territorial Planning New Economic Decisions of the Council of Ministers The 92nd Anniversary of Bulgaria's Liberation from Turkish Rule Changes in the Regulations on Distribution of Scholarships Comings and Goings Agreements Signed